Generalizing the Taylor Principle: Reply - Davig, Troy; Leeper, Eric M (American Economic Review, 2010)
Farmer, Waggoner, and Zha (2009) (FWZ) show that a new Keynesian model with regime-switching monetary policy can support multiple solutions, appearing to contradict findings in Davig and Leeper (2007) (DL). The explanation is straightforward: FWZ derive solutions using a model that differs from the one to which the DL conditions apply. The FWZ solutions also require that the exogenous driving process is a function of private and policy parameters. This undermines the sharp distinctions among “deep parameters” typical of optimizing models and makes it difficult to ascribe economic interpretations to FWZ's additional solutions. (E12, E31, E43, E52)